The role of occupational health services in the universal health coverage era in Indonesia - Mansyur, Muchtaruddin (Universa Medicina, 2019)
In accordance to Act No 24 Year 2011 on The Social Security Administrating Body, the Indonesian National Social Security program is managed by  two national organizations, namely: Social Security Administering Body for Health (Badan Penyelenggara Jaminan Sosial Kesehatan = BPJS Kesehatan) and Social Security Administering Body for Labor (Badan Penyelenggara Jaminan Sosial Ketenagakerjaan = BPJS Ketenagakerjaan). The former is responsible for providing health coverage for all Indonesians through the National Social Health Insurance Scheme known as the Jaminan Kesehatan Nasional/JKN. The latter is  responsible for  providing the worker's social security consisting of Provident Fund Benefit, Accident Benefit, Pension Benefit, and Death Benefit.1The Indonesian government has been continuously improving the health service program towards better national universal health coverage and has set the 2019 functional achievement target of 95% of the population enrolled in the program. To ensure that this target of  the program will be achieved,  the government pays the premium of BPJS Kesehatan of the poor and near poor.2